Heterologous expression and initial in silico characterization of a novel snakin-Z peptide - TURAN, KADİR (My University, 2023)
Heterologous expression of the plant-derived snakin-Z (SNK-Z) peptide was carried out inEscherichia coliBL21 and Mach 1 strains using the pET14b, and pGEX-6P-1 vectors, and its tertiary structure was determined. The most efficient production of the recombinant fusion peptide (GST/SNK-Z) in both strains was achieved by induction with 0.1 mM isopropyl β-D-1-thiogalactopyranoside at 32°C. GST/SNK-Z with 30.14kDa which yielded 6.5mg/L protein, was purified by affinity chromatography followed by dialysis. The GST tags were removed using PreScission protease. The IC50of GST/SNK-Z was calculated as 12.07 µM forStaphylococcus aureus(ATCC 25923) using nonlinear regression analysis. The secondary structure of recombinant SNK-Z consisted of α-helix and coil sites. It’s 3-D model was generated with a confidence score of -0.20 and a template modeling score of 0.69 ± 0.12. The predicted solvent accessibility and B-factor profile were detected.This is the first report of heterologous expression of SNK-Z inE. coli. Our study provides fundamental data for the large-scale production of SNK-Z, which has a high potential for use in the pharmaceutical industry because of its previously reported antimicrobial effects.
Keywords: Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Temel Bilimler; Life Sciences; Biotechnology; Molecular Biology and Genetics; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Mikrobiyoloji; ÇOK DİSİPLİNLİ BİLİMLER; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; MULTIDISCIPLINARY SCIENCES; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Moleküler Tıp; Moleküler Biyoloji; Multidisipliner; Applied Microbiology and Biotechnology; Molecular Medicine; Molecular Biology; Multidisciplinary